2012
DOI: 10.1099/ijs.0.026302-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic descriptions of three marine colepid ciliates, Nolandia sinica spec. nov., Apocoleps caoi spec. nov. and Tiarina fusa (Claparède & Lachmann, 1858) Bergh, 1881 (Ciliophora, Prorodontida)

Abstract: The morphology of three marine colepid ciliates, Nolandia sinica spec. nov., Apocoleps caoi spec. nov. and Tiarina fusa (Claparède & Lachmann, 1858) Bergh, 1881, isolated from Chinese coastal waters, was investigated. N. sinica spec. nov. may be separated from its congeners by the structure of its armour plates, each of which may have up to five reniform windows. A. caoi spec. nov. is characterized by its large body with broad anterior end and by having 10–12 long, sharp posterior spines. New data and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Compared with T. fusus, the newly isolated ciliate has a larger length-to-width ratio (1.5 times more), lacks armor spines and possesses long somatic cilia arranged in 18 or more ciliary rows (T. fusus has 15-17 longitudinal rows; Supplementary Table S7). As shown by brightfield (on more than 50 cells) and confocal (on 10 cells) microscopy images (Figures 1d and e and Supplementary Figure S2), another distinct morphological character of the isolated ciliate is the presence of 10 to 25 intracellular microalgal cells that has never been reported in T. fusus (Foissner et al, 2008;Lynn, 2008;Chen et al, 2012). Kahl (1930) observed 'ingested dinoflagellates' ('Nahrung kleine Peredineen') in the arctic species T. meunieri but this old and succinct description has not been confirmed in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with T. fusus, the newly isolated ciliate has a larger length-to-width ratio (1.5 times more), lacks armor spines and possesses long somatic cilia arranged in 18 or more ciliary rows (T. fusus has 15-17 longitudinal rows; Supplementary Table S7). As shown by brightfield (on more than 50 cells) and confocal (on 10 cells) microscopy images (Figures 1d and e and Supplementary Figure S2), another distinct morphological character of the isolated ciliate is the presence of 10 to 25 intracellular microalgal cells that has never been reported in T. fusus (Foissner et al, 2008;Lynn, 2008;Chen et al, 2012). Kahl (1930) observed 'ingested dinoflagellates' ('Nahrung kleine Peredineen') in the arctic species T. meunieri but this old and succinct description has not been confirmed in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…From 20 cells, various morphological characters were observed with scanning electron microscopy, notably an armored skeleton composed of calcium carbonate plates (Figures 1a and b), indicating that the ciliate belongs to the family Colepidae Ehrenberg, 1838 (class Prostomatea, order Prorodontida; Lynn, 2008;Chen et al, 2012). A morphological comparison with six previously described ciliate species from the family Colepidae (Coleps hirtus, Nolandia nolandi, Apocoleps magnus, Levicoleps biwae, Tiarina meunieri and Tiarina fusus) indicated that T. fusus is the species that most closely resembles the ciliate isolated in this study (Supplementary Table S7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations